PERANAN INOVASI SEBAGAI MEDIATOR PADA KINERJA USAHA CAFÉ - Christian, Michael (Jurnal Pengabdian dan Kewirausahaan, 2019)
Research data shows that in the Southeast Asian region, Indonesia is the largest country in terms of the foodservice market with sales figures increasing from 2010-2014. This indicates that even though this trend was followed by the "loss of time" of food service businesses in Indonesia, the food service market still has markets and enthusiasts who are always there. Cafes in the Indonesian food service market increased from a compound year growth rate (CAGR) of 9.4% in sales from 2010 to 2014, reaching US $ 3.6 billion in 2014, and are expected to continue to increase sales value at 9 CAGR, 7% from 2015 to 2019. Sales in café businesses are second in the food service subsector in Indonesia. This explains that there is a large enough market for business opportunities especially when looking at the number of outlets and the number of existing transactions. The development of information technology cannot be separated in the formation of a new concept of business marketing and sales in the form of cafes. This study aims to analyse the impact of innovation as a mediator on cafe business performance and other factors that influence business performance. This study uses Partial L east Square - Structural Equation Modelling (SEM) using SMART PLS 3.0. The results of this study explain that the business performance of cafes in the Central Jakarta area is influenced by Customer Orientation. Furthermore, the café business performance in the Central Jakarta area is influenced by Innovation. The third thing is that innovation is influenced by customer orientation factors. Furthermore, the fourth conclusion is that the business performance of cafes in the Central Jakarta area is influenced by customer orientation which is mediated by the Innovation factor.Keywords: business performance, customer orientation, innovation